Lime Peel Liquid (Citrus aurantifolia, Swingle) Inhibit Escherichia Coli In Vitro - Sari, Devi Indah; Wahjuni, Retno Sri; Praja, Ratih Novita; Utomo, Budi; Wibawati, Prima Ayu (Universitas Airlangga, 2021)
The purpose of this study was to determine in vitro inhibition test of lime peel liquid (Citrus aurantifolia, Swingle) against E. coli. The E. coli isolate was cultured on Muller Hinton Agar (MHA) media. Antibacterial test in this study using diffusion method. Negative control (K-) using CMC-Na 0.1%. Positive control (K+) using oxytetracycline antibiotics. The treatments were given lime peel liquid (Citrus aurantifolia, Swingle) with concentrations of 100%, 75%, 50% and 25%, respectively. The study design using Completely Randomized Design (CRD) method, with six treatments and four repetitions. Data were analyzed by Kruskal-Wallis test, Moreover, the Post Hoc Mann-Whitney method. The inhibition zone analysis results were showed that K + had significant differences compared to all treatments K-, 100%, 75%, 50%, and 25%. K- was found to be significantly different from treatments 100%, 75%, 50% and 25%. The results showed that the lime peel liquid has the potential as an antibacterial activity against the growth of E. coli in vitro. Concentration of 25% has shown the presence of inhibitory zones on Mueller Hinton media that have been inoculated with lime peel liquid.